Single OTRA Based Analog Multiplier and Its Applications. (11th November 2012) - Pandey, Rajeshwari; Pandey, Neeta; Sriram, B.; Paul, Sajal K.
Abstract : This paper presents an analog multiplier using single operational transresistance amplifier (OTRA). The proposed circuit is suitable for integration as it does not use any external passive component. It can be used as a four-quadrant multiplier. Theoretical propositions are verified through PSPICE simulations using 0.5 μ m CMOS parameters provided by MOSIS (AGILENT). The simulation results are in close agreement with theoretical predictions. The workability of the proposed multiplier is also tested through two applications, namely, a squarer and an amplitude modulator.